Evaluating the effectiveness of supply chain simulation exercises in public health - a case study perspective - Adjahi, Lucile (Cranfield University, 2025)
Accompanied by a United Nations Organisation, this thesis investigates how operational exercises (OpExs) contribute to learning and performance at individual, organisational, and systemic levels in humanitarian health supply chains, focusing on three large-scale OpExs in Malawi involving over 100 participants from more than 25 organisations. Leveraging the Knowledge Creation Theory (KCT), it examines how knowledge is generated, transferred, and institutionalised across these levels. A qualitative case study approach was used, combining key informant interviews, focus group discussions and document analysis. Findings show that the operational exercises enhance preparedness through three linked pathways: building individual skills and decision-making confidence, embedding lessons into organisational routines and systems, and strengthening system-wide coordination via shared procedures, trust, and communication channels. However, training benefits are often short-lived if learning is not deliberately captured, codified, and shared. Cross-agency interactions emerged as more influential than internal processes for fostering systemic resilience. The study extends KCT to humanitarian, high-pressure, multi-stakeholder contexts in low- and middle-income countries, revealing that learning cycles are iterative, adaptive, and shaped by scenario design, trust, and operational constraints. Practical recommendations are offered to improve design and reduce training transfer failure. Overall, the research demonstrates that well-designed, context-specific OpExs can significantly improve the effectiveness and impact of humanitarian supply chains, thereby enhancing the timeliness and appropriateness of responses to crises.
Keywords: Knowledge Creation Theory; humanitarian logistics; training evaluation; knowledge transfer; operational exercises